Progress status for the Mu2e calorimeter system. (13th February 2015) - Pezzullo, Gianantonio; Budagov, J; Carosi, R; Cervelli, F; Cheng, C; Cordelli, M; Corradi, G; Davydov, Yu; Echenard, B; Giovannella, S; Glagolev, V; Happacher, F; et al.
Abstract: The Mu2e experiment at FNAL aims to measure the charged-lepton flavor violating neutrinoless conversion of a negative muon into an electron. The conversion results in a monochromatic electron with an energy slightly below the muon rest mass (104.97 MeV). The calorimeter should confirm that the candidates reconstructed by the extremely precise tracker system are indeed conversion electrons while performing a powerful μ /e particle identification. Moreover, it should also provide a high level trigger for the experiment independently from the tracker system. The calorimeter should also be able to keep functionality in an environment where the background delivers a dose of 10 krad/year in the hottest area and to work in the presence of 1 T axial magnetic field. These requirements translate in the design of a calorimeter with large acceptance, good energy resolution O(5%) and a reasonable position (time) resolution of < 1 cm (<0.5ns). The baseline version of the calorimeter is composed by two disks of inner (outer) radius of 351 (660) mm filled by 1860 hexagonal BaF2 crystals of 20 cm length. Each crystal is readout by two large area APD's. In this paper, we summarize the experimental tests done so far as well as the simulation studies in the Mu2e environment.